Kinetic Fluorescence Determination of Formaldehyde in Water Samples - Zhao, Q.; Chen, L.H. (Asian Journal of Chemistry, 2013)
A novel kinetic fluorescence analytical method for determination formaldehyde in environmental water samples has been developed. It was based on the catalytic effect of formaldehyde for the oxidation of thionine by potassium bromate, leading to the colour fading and fluorescence weakening in hydrochloric acid medium. Under the optimized conditions, the limit of determination, based on three times of the standard deviation of the reagent blank, was 5.8 μg/L. The calibration graph of linear was in the range of 10.0-300 μg/L. The method was applied to the detection of formaldehyde in environmental river water and well water, the recovery of river water samples were in the range of 98.3-101.6 % and the recovery of well water samples were in the range of 97.6-102.8 %.